Individual adenovirus type 5 early region 1A gene products elicit distinct alterations of cellular morphology and gene expression. - Roberts, B E (1985)
Adenovirus early region 1A (E1A), which gives rise to three overlapping transcripts, was inserted into a murine leukemia virus-derived vector, and recombinant viruses were used to prepare permanent cell lines of NIH 3T3 cells containing DNA copies of the individual 13S, 12S, and 9S mRNAs. Integrated proviral copies of the recombinant genomes were rescued as bacterial plasmids from each of the cell lines, and the DNA sequence of E1A was demonstrated to be a precise copy of the individual transcripts. The DNA copies were shown to be expressed as part of the full-length retroviral transcript by S1 nuclease analysis, and the synthesis of their encoded polypeptides was demonstrated by immunoprecipitation. Those cell lines expressing the polypeptide encoded by the 13S transcript were shown to contain that function required for regulating the accumulation of mRNAs from adenovirus early genes by their ability to complement the adenovirus type 5 E1A deletion mutant dl312. Cell lines expressing polypeptides encoded by the 13S, 12S, and 9S transcripts showed characteristic alterations in morphology. Two-dimensional gel electrophoresis of total cellular protein derived from the three cell lines demonstrated that each E1A gene product elicits specific alterations in the patterns of proteins expressed. Studies of the expression of two specific genes, those encoding fibronectin and collagen type 1, indicated that the observed alteration in levels of the two proteins results from a reduction in RNA levels induced by E1A functions.